A atualidade da questão agrária: a luta pela terra e a produção das camponesas e dos camponeses do acampamento terra livre no município de Clevelândia – Pr - Folador, Matheus Flaherty (2024)
The present research aims to understand the current state of agrarian issues, identifying the struggle for land and the production of peasant farmers in the Terra Livre Encampment of the Landless Rural Workers' Movement (MST), in the municipality of Clevelândia, Paraná, Brazil, seeking to contextualize Brazil’s territorial formation process through land concentration and land grabbing, presenting the agrarian reform policy in Brazil post 2016 impeachment, identifying not only the formation process of the MST, the methods of land struggle, and resistance emerging from land conflicts, but also the process of resistance, organization, and production of the peasant farmers at the Terra Livre Encampment. To achieve these objectives, we conducted a literature review, researching and analyzing scientific works on the topics addressed as well as the materials produced by the MST itself. In addition to the bibliographic research, we conducted semi-structured interviews with the peasant farmers at the Encampment, during fieldwork and immersion internship, in order to discuss their ways of life based on their own accounts and experiences. Thus, the research contributes to the debate on the current relevance of agrarian issues and the necessity of agrarian reform in both the country and the Southwest region of Paraná, addressing the organization and production of peasant farmers who have resisted various forms of violence, both from the state and hired gunmen, and remain on the land, struggling for working land, creating territorialities, and producing food.